1995
DOI: 10.1016/s0006-3495(95)80385-1
|View full text |Cite
|
Sign up to set email alerts
|

Photocycle of halorhodopsin from Halobacterium salinarium

Abstract: The light-driven chloride pump, halorhodopsin, is a mixture containing all-trans and 13-cis retinal chromophores under both light and dark-adapted conditions and can exist in chloride-free and chloride-binding forms. To describe the photochemical cycle of the all-trans, chloride-binding state that is associated with the transport, and thereby initiate study of the chloride translocation mechanism, one must first dissect the contributions of these species to the measured spectral changes. We resolved the multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
94
3

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(109 citation statements)
references
References 69 publications
(79 reference statements)
12
94
3
Order By: Relevance
“…HsHR served as a negative control because of the inability of the light-driven proton transportation to generate a protein-based photocurrent. In addition, the photocycle of HsHR was shown to lack the O state; alternatively, another possibility mentioned in a previous study is that the O state might have occurred too rapidly to be detected (16). Therefore, HsHR might undergo both Cl À release and reuptake processes during the N-state decay (30).…”
Section: Simultaneous Recording Of Flash-laser-induced Photocycle Andmentioning
confidence: 85%
See 1 more Smart Citation
“…HsHR served as a negative control because of the inability of the light-driven proton transportation to generate a protein-based photocurrent. In addition, the photocycle of HsHR was shown to lack the O state; alternatively, another possibility mentioned in a previous study is that the O state might have occurred too rapidly to be detected (16). Therefore, HsHR might undergo both Cl À release and reuptake processes during the N-state decay (30).…”
Section: Simultaneous Recording Of Flash-laser-induced Photocycle Andmentioning
confidence: 85%
“…First, crystal structures have been solved for HsHR (12,13) and NpHR (14), and revealed that these HRs differ in the location of their secondary anion binding site (14)(15)(16). Second, substitution of chloride with azide was found to affect the photoreactions of the two proteins differently (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Ion-pumping rhodopsins transport one ion during a single turnover of photocycle and generally undergo fast photocycles (Ͻ100 ms), which enable the generation of a large transmembrane electrochemical potential under constant illumination. On the other hand, similar to HR and FR, no absorbance change at 400 nm was observed throughout the photocycle (14,34,36) The slow photocycle of MrHR might reflect some differences in the physiological role from other Cl Ϫ -pumping rhodopsins. Although the details are not fully resolved, the Cl Ϫ pumps are believed to play roles in light-driven ATP production and/or maintaining the cellular osmotic balance during the volume increase of the growing cell (38 -41).…”
Section: Rhodopsin Cannot Transport It This Indicates That Mrhr Funcmentioning
confidence: 98%
“…They show similar absorption spectral changes during their photocycles (17), indicating that the retinal is in a similar conformation and electrostatic environment (19). Five of six spectroscopically identified BR intermediates are found in HR (20).…”
mentioning
confidence: 91%